Expressão da atitude através da prosódia em indivíduos com doença de Parkinson idiopática - Luciana Lemos de Azevedo (2007)
Patients with Parkinson disease (PD) show a significant frequency of changes of voice and speech. The present study had as its aim to investigate the prosodic parameters used in the expression of attitudes by subjects with idiopathic PD (IPD) and to study the effect of levodopa and a modified method of Lee Silverman Voice Treatment in comparison with healthy controls. Ten patients with IPD and ten matched healthy controls were enrolled in the study. All subjects underwent the recording of the corpus in an acoustically prepared environment, where they were asked to pronounce three statements related to a context: expressing the attitude of certainty (AC), expressing the attitude of doubt (AD), expressing the declarative mode (DM) and expressing the interrogative mode (IM). The results showed that in the comparison between the DM and the AC, and between the AM and the AD, only the control group (CG) showed an increase in the amplitude of the melodic variation of the pre-tonic unstressed vowel in the expression of the AC. When the parameters of each of the subjects of CG was analyzed individually, it could be noticed that all of them showed one to three variables which distinguished DM from AC and IM from AD, suggesting that the manipulation of the prosodic parameters to express the attitudes is an individual feature. Taking into account the patients with PD, no prosodic behavior that could characterize the expression of attitudes (when comparing the DM to the AC, and the IM to the AD) was observed. Nevertheless, when all attitudes (certainty and doubt) were compared with all modes (declarative and interrogative), it was observed a longer duration to express the attitudes. When studying the use of prosodic parameters by these subjects, disregarding the attitudes, it was observed that PD impairs the production of the prosodic parameters. After the administration of levodopa, it was noticed a significant improvement of the parameters of duration, but even so the patients did not achieve a performance as satisfactory as that of CG. The pharmacological treatment improved the parameters of duration and the speech therapy provided more benefits to the variable fundamental frequency whereas the association of treatments (pharmacological and speech therapy) improved all the prosodic parameters: fundamental frequency, duration and intensity. In all the comparison performed, it was observed that the statements of DM and AC presented the highest value of fundamental frequency in the pre-tonic unstressed vowel (except for the expression of the AC for the female informants of the CG, whose highest value occurred in the nuclear tonic), while statements of the IM and the AD presented with the highest value of the fundamental frequency in the nuclear tonic.